Values, social relations and rules of social control between the real and virtual communities - Al-ali, Adil (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The present study aims to identify the nature of virtual relationships and their distinctive characteristics, and to identify the reasons behind the rush of large numbers of people to join the virtual society and to engage in various economic, social, emotional and financial relations, establishing a parallel situation of common relations in the real community. The research also seeks to explore whether values ​​as rules and guidelines for behavior and social relationships in the living societies play the same role in the virtual society? Is the voluntary resort to the virtual society is a voluntary withdrawal from the real society, or merely a transient leap? The researcher mainly used the comparative and historical analysis method, to answer the research questions which formed the research problem, and the results of the basic and secondary assumptions and their validation , and the desired goals. The comparative method is common in research and social studies that seek to reveal similarities and differences regarding specific phenomena that are already forming or have already been formed. This is fully applicable to our current study. The historical approach serves in returning to the distant or near past to identify the techniques of communication and social networking and put all this in the right context according to the requirements of the research and its necessities and purpose.